Pengembangan Bahasa Anak Usia Dini Melalui Metode Bermain Peran di Desa Simangambat Kecamatan Siabu Kabupaten Mandailing Natal - Ummi Kalsum; Dinil Arifah; Marlina, Marlina (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This study aims to explore the development of language in early childhood through the role-playing method in Simangambat Village, Siabu District, Mandailing Natal Regency. Role-playing was chosen because it effectively helps children learn language actively, contextually, and introduces them to social roles in everyday life. Observations were made on children involved in role-playing activities such as acting as farmers, digging, planting rice, and engaging in trade. The results show that role-playing can enhance children's language skills, including speaking, listening, and understanding words within their social context. Furthermore, this method also stimulates creativity, critical thinking, and strengthens social skills such as empathy and cooperation. The study provides valuable insights into the benefits of role-playing in early childhood language development, particularly in rural communities, and is expected to contribute to the development of more effective educational strategies in rural settings.